Extraction and characterization of pectin from passion fruit peels - Liew, Shan Qin; Chin, Nyuk Ling; Yusof, Yus Aniza (Elsevier, 2014)
The influence of pH and extraction time on pectin yield and composition was studied in a citric acid extraction process. The pectin yield and degree of esterification (DE) of the extracted pectin ranged from 2.25 to 14.60% and 41.67 to 67.31% respectively. It was found that extraction pH was the most important parameter influencing yield. DE was significantly affected by extraction time. Morphological analysis performed using scanning electron microscopy suggested that the dried passion fruit pectin has a smooth surface with little mound-shaped pellets on it.